THE TRANSFORMATION OF UNDERSTANDING THE TRANSCENDENCE IN THE HISTORY OF EUROPEAN CULTURE - Морозов, А. Ю. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Such notions as ordinary world, transcendence, transcendental ideal, Other, essence, existence, initiation, mythopoeia are analyzed in this article.